The interphase chromatin special state zones - Shpilevaya, S. P.; Kostetsky, I. E.; Bilitch, K. M.; Lihatcheva, L. I.; Stolar, T. V.; Irodov, D. M.; Kostetskaya, E. V.; Spivak, I. M.; Zhestyanikov, V. D.; Kordyum, V. A. (Биополимеры и клетка, 1993)
The possibility is demonstrated of RecA protein of E. coli introduction into eukaryotic cell with preservation of its biologicall activity. The character of this protein affinity to chromatin of different degree of condensation is shown on cytological level (undirect immunofluorescent method combined with cytophotometry) for different stages of cellular cycle (protein is not tested in meta- and anaphase chromosomes). The presence of bacterial RecA protein in the nuclei and cytoplasm of cells both in vitro and in vivo is confirmed with the help of immunoelectron microscopy. Studies were carried out on cultures of HeLa and Ltk⁻ cells and also in vivo on hepatocytes after direct injection on RecA protein and plasmid pKCR2 enclosed in liposomes into the liver of adult mice line BALB/c. Proceeding from the experimental data obtained and also considering the fact that RecA protein mainly connects with single-stranded DNA, the assumption is done about existence of special state chromatin zones (SSCZ). For these zones the active affinity to RecA protein serum is character with intensive fluorescence, thus they may correspond to some actively expressing genes, gathered in clusters. Показано можливість введення до еукаріотичної клітини RecA-білка Е. coli із збереженням його біологічної активності. На цитологічному рівні (непрямий імунофлюоресцентний метод з цитофотометрією) визначено характер зв'язування RecA- білка з хроматином різного ступеню спіралізації на окремих стадіях клітинного циклу (у мета- і анафазних хромосомах білок не тестується). Присутність бактеріального білка у цитоплазмі і ядрах клітин in vivo та in vitro підтверджена також імуноелектронною мікроскопією. Виходячи з отриманих експериментальних даних та враховуючи переважне зв'язування RecA-білка з онДНК, зроблено припущення про існування зон особливого стану хроматина (ЗOCX), які характеризуються активним зв'язуванням з сироваткою до бактеріального RecA-білка та інтенсивною флюоресценцією і можуть відповідати зібраним у кластери активно експресуючим генам. Експерименти виконано на культурах клітин HeLa і Ltk⁻, а також in vivo на гепатоцитах після прямого введення білка та плазміди pKCR2 у складі ліпосом до печінки дорослих мишей лінії BALB/c. Показана возможность введения в эукариотическую клетку RecA - белка Е. coli с сохранением его биологической активности . На цитологическом уровне (непрямой иммунофлюоресцентный метод с цитофотометрии ) определен характер связывания RecA - белка с хроматином разной степени спирализации на отдельных стадиях клеточного цикла (в мета- и анафазного хромосомах белок не тестируется ) . Присутствие бактериального белка в цитоплазме и ядрах клеток in vivo и in vitro подтверждено также имуноэлектронной микроскопией . Исходя из полученных экспериментальных данных и учитывая преимущественное связывание RecA - белка с онДНК , высказано предположение о существовании зон особого состояния хроматина ( ЗOCX ) , которые характеризуются активным связыванием с сывороткой к бактериальному RecA - белка и интенсивной флюоресценцией и могут соответствовать собранным в кластеры активно экспрессирующим генам . Эксперименты выполнены на культурах клеток HeLa и Ltk⁻ , ??а также in vivo на гепатоцитах после прямого введения белка и плазмиды pKCR2 в составе липосом в печени взрослых мышей линии BALB/c.